Carinal resection - Petrov, Roman V. (Shanghai Chest, 2018)
Tracheobronchial tumors with involvement of the carina represent a challenging problem in the pulmonary surgery. Carinal resection is referred to removal and reconstruction of the airway itself, whereas concomitant removal of the lung parenchyma (usually a whole lung) is termed as carinal pneumonectomy. Thorough preoperative workup of these patients is mandatory. Meticulous surgical technique and aggressive postoperative management is required for the best outcomes in these difficult cases. In the paper authors review surgical technique, evaluation and management of this challenging patient population.